Potret Wanita Unggul dalam Karya Sastra Naratif Tradisional - Duana Sutika, I Nyoman; Sulibra, I Ketut Ngurah (Humanis; Vol 27 No 2 (2023), 2023)
The paper wants to inspire and awaken the enthusiasm and potential of women so that they can compete in quality in people's lives. Women have the opportunity to make themselves superior, qualified, and have bargaining values ??in the life of society and the state, if they develop awareness and a spirit of competition, forming themselves into intelligent, strong and independent women. This is reflected in the figures of Ni Diah Tantri in Tantri Carita, Ni Wayan Puyung Sugih in Geguritan Puyung Sugih, and Dewi Drupadi (Pancali) in the Mahabharata. These three figures are able to show their quality as elected women with adequate self-quality. Women who are able to dominate people of their own kind and even the opposite sex and go through and solve other complicated problems.